(untitled) (Journal of Current and Advance Medical Research, 2019)
Background: Haemorroid stapler becomes easier and safe to deal multiple and prolapsed haemorrhoid at a time. Objectives: The purpose of the present study was to evaluate the outcome of suture haemorrhoidopexy for secondary position haemorrhoids in addition to haemorrhoidectomy for primary haemorrhoids (multiple). Methodology: This prospective interventional study was performed in Dhaka Medical College Hospital, Dhaka, Bangladesh and in a private hospital in Gazipur, Bangladesh for over five (05) years from January 2012 to December 2016. Patients who were presented with secondary position haemorrhoids in addition to primary position haemorrhoids (multiple haemorrhoids) were included in this study. Open haemorrhoidectomy (Milligan-Morgan) followed by suture haemorrhoidopexy was done. All patients were followed up after 1, 2, 4, 8 weeks, 6 months and 1 yearly. Result: Total 18 patients were operated. Among those immediate complications were encountered in patients in the form of per rectal bleeding 1(5.55%), pain 3(visual pain scale 4)16.66%, mucosal oedema 6(33.33%), no patient developed early postoperative prolapse. No patient developed bowel incontinence. Late complications experienced as prolapse at 1 year follow up which was treated by conservative measures. No patient developed anal stenosis. Mean operating time was 25 minutes and duration of hospital stay was 1 day. Conclusion: Stapled haemorrhoidopexy is a safe procedure for circumferential excision of mucosa and submucosa dealing all haemorrhoids and prolapse simultaneously. Journal of Current and Advance Medical Research 2019;6(2): 73-76